In Vivo Efficacy of a "Smart" Antimicrobial Implant Coating. (20th July 2016) - Stavrakis, Alexandra I.; Zhu, Suwei; Hegde, Vishal; Loftin, Amanda H.; Ashbaugh, Alyssa G.; Niska, Jared A.; Miller, Lloyd S.; Segura, Tatiana; Bernthal, Nicholas M.
Abstract : Background: Postoperative infection is a devastating complication following arthroplasty. The goals of this study were to introduce a "smart" implant coating that combines passive elution of antibiotic with an active-release mechanism that "targets" bacteria, and to use an established in vivo mouse model of post-arthroplasty infection to longitudinally evaluate the efficacy of this polymer implant coating in decreasing bacterial burden. Methods: A novel, biodegradable coating using branched poly(ethylene glycol)-poly(propylene sulfide) (PEG-PPS) polymer was designed to deliver antibiotics both passively and actively. In vitro-release kinetics were studied using high-performance liquid chromatography (HPLC) quantification in conditions representing both the physiologic environment and the more oxidative, hyperinflammatory environment of periprosthetic infection. The in vivo efficacy of the PEG-PPS coating delivering vancomycin and tigecycline was tested using an established mouse model of post-arthroplasty infection. Noninvasive bioluminescence imaging was used to quantify the bacterial burden; radiography, to assess osseointegration and bone resorption; and implant sonication, for colony counts. Results: In vitro-release kinetics confirmed passive elution above the minimum inhibitory concentration (MIC). A rapid release of antibiotic was noted when challenged with an oxidative environment (p < 0.05), confirming a "smart" active-release mechanism. The PEG-PPS coating with tigecycline significantly lowered the infection burden on all days, whereas PEG-PPS-vancomycin decreased infection on postoperative day (POD) 1, 3, 5, and 7 (p < 0.05). A mean of 0, 9, and 2.6 × 10 2 colony-forming units (CFUs) grew on culture from the implants treated with tigecycline, vancomycin, and PEG-PPS alone, respectively, and a mean of 1.2 × 10 2, 4.3 × 10 3, and 5.9 × 10 4 CFUs, respectively, on culture of the surrounding tissue (p < 0.05). Conclusions: The PEG-PPS coating provides a promising approach to preventing periprosthetic infection. This polymer is novel in that it combines both passive and active antibiotic-release mechanisms. The tigecycline-based coating outperformed the vancomycin-based coating in this study. Clinical Relevance: PEG-PPS polymer provides a controlled, "smart" local delivery of antibiotics that could be used to prevent postoperative implant-related infections.